PENGARUH EFEKTIVITAS KOMITE AUDIT TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN. (Studi Empiris Pada Perusahaan Yang Terdaftar di IDX30 BEI Tahun 2016-2018). - Angel Siregar; Romulo Sinabutar (Fakultas Ekonomi Universitas Advent Indonesia, 2019)
The purpose of this study was to determine the effect of the effectiveness of the audit committee on the timeliness of delivering financial reports on IDX30. The research method is descriptive with a quantitative approach. The number of samples is 18 companies in accordance with the criteria established by the author. The results showed that the number of members of the audit committee had fulfilled the requirements set by the government. Likewise, all of these companies did not experience delays in financial reporting to the IDX except BCA and BSD. In the partial test and simultaneous test it was found that the variable X had no significant effect on the variable Y.